Begin risk assessment for falls in women at 45, not 65. Issue 3 (23rd July 2018) - Harmon, Katherine J; Hakenewerth, Anne M; Waller, Anna E; Ising, Amy; Tintinalli, Judith E
Abstract : The clinical and epidemiological literature provides guidelines for fall prevention starting at age 65; however, the focus on age ≥65 is not evidence based. Therefore, this study examined state-wide North Carolina emergency department visit data to examine the characteristics of falls across the age spectrum, identify the age at which the incidence of fall-related emergency department visits started to increase and determine whether these trends were similar for men and women. We determined that incidence rates of fall-related emergency department visits began to increase in early middle age, particularly for women. Since fall risk assessment and prevention activities should be initiated prior to an injurious fall, we recommend beginning these activities before age 65.